Callusing and regeneration response of in vitro derived leaf explants of gerbera (Gerbera jamesonii) - MAHINDRAKAR, AAKANKSHA; KUMAR, RAJIV; ASWATH, C; MUNIKRISHNAPPA, P M (The Indian Journal of Agricultural Sciences, 2018)
Gerbera (Gerbera jamesonii Bolus ex. Hookes F.) is one of the most popular commercial flowers worldwide used both as cut flower and potted plant. Conventionally, it is propagated through vegetative means such as divisions of clump which is very slow process and not commercially viable. Rapid multiplication of elite hybrids/genotypes with improved quality traits, has been achieved by using both direct and indirect tissue culture methods. Gerbera hybrid seeds obtained by half-sib mating were raised in half strength MS medium. The earliest days for seed germination (2.00), first leaf development (3.00 days) and rooting (3.00 days) was recorded line IIHR1-1, IIHR 5-4 and IIHR1-1, IIHR1-2, IIHR1-5, IIHR3-2 and IIHR5-4. The response of in vitro leaf explants to callusing and regeneration was recorded when cultured on full strength Murashige and Skoog’s media supplemented with different concentrations of 2,4-D or BAP or IAA and Kinetin. Leaf explants cultured on MS medium fortified with equal concentration of BA (1 mg l-1) and 2, 4-D (1 mg l-1) produced green and greenish white granular callus within 25 days, however, leaf explants cultured on MS medium supplemented with 2,4-D produced yellowish callus. Plant regeneration was also found earliest in the same media within 14 days.